Propuesta de Aplicación del Diseño Integral a la Creación de La Colección de Joyas Basada En las Especies Protegidas de la Reserva Yasuní, Apoyando a la Iniciativa Yasuní ITT - Goyes Villalva, Alison Natalia (2014)
The following job has the purpose to recreate the biodiversity of Yasuní ITT project by designing a jewelry collection based on representative birds of the Yasuní National Park, showing the graphical richness that these legendary birds possess and contribute to the design. Is to capture their essence through a unique piece of jewelry using precios metals like gold, silver and copper, as well as its value and importance of their existence.